Efeitos causados por nanopartículas de La2O3 em Pfaffia glomerata (Spreng.) Pedersen e estudo da distribuição de elementos por LA-ICP-MS - Neves, Vinicius Machado (2018)
The effect of La2O3 nanoparticles (NP-La2O3) on plants of the species Pfaffia glomerata (Spreng.) Pedersen was investigated. Besides, the translocation and the distribution of the NPs in aerial parts of the plant were evaluated. Element determination and its distribution (bioimaging) of elements in leaves and stem were performed by laser ablation inductively coupled plasma combined mass spectrometry (LA-ICP-MS). The main innovation of the work is associated on the study of the effects of NPs on vegetables and those caused by La. Therefore, studies on root and shoot growth, and concentrations of pigments and nutrients were carried out after in vitro micropropagation of P. glomerata cultivated for 28 days in the presence of 0, 50, 100, 200 and 400 mg L-1 of NP-La2O3 and nonnanoparticulate La2O3 (NN-La2O3). LA-ICP-MS allows the direct analysis of solid materials with minimal sample manipulation, and one of its applications is the production of bioimaging to verify the distribution of chemical elements in plant tissues in qualitative and quantitative form. It was possible to observe the distribution of Ca, Cu, Fe, La, Mg, Mn, Mo, P, S and Zn in leaves of P. glomerata, where results indicated that, at least, part of La uptake by the plant is in the form of NP-La2O3.